Land Optimization With Sweet Corn (Zea mays saccharata, Sturt) and Eggplant (Solanum melongena L.) Overlapping Systems in Nagari Gadut, Tilatang Kamang District - Desi Ratna Sari; Yurma Metri (Fakultas Pertanian Universitas Muara Bungo, 2023)
Research conducted experiment using a completely randomized design with 6 treatments that is the time of planting eggplant as secondary crops to the cultivation of sweet corn (M) consisting of: M1 = planting at same time; M2 = time of planting eggplant 1 week after planting sweet corn; M3 = time of planting eggplant 2 weeks after planting sweet corn; M4 = time of planting eggplant 3 weeks after planting sweet corn; M5 = single planting sweet corn planting time = M1. M6 = single eggplant planting time = M1. The results planting showed that eggplant can be planted together with sweet corn planting time, up to three weeks after planting sweet corn. Results of sweet corn is not influenced by the timing of planting different eggplant. The M3 and M4 treatments resulted in relatively more profitable production based on the total relative yield (RYT) and land equivalent ratio (LER).